2022
DOI: 10.1111/1541-4337.12980
|View full text |Cite
|
Sign up to set email alerts
|

Analytical strategies for the determination of biogenic amines in dairy products

Abstract: Biogenic amines (BA) are mainly produced by the decarboxylation of amino acids by enzymes from microorganisms that emerge during food fermentation or due to incorrectly applied preservation processes. The presence of these compounds in food can lead to a series of negative effects on human health. To prevent the ingestion of high amounts of BA, their concentration in certain foods needs to be controlled. Although maximum legal levels have not yet been established for dairy products, potential adverse effects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 246 publications
(335 reference statements)
0
11
0
Order By: Relevance
“…Multiple analytical methods have been developed to determine these compounds in various foods and beverages. Many review papers have been written in recent years [ 40 , 41 , 42 ]. Chromatographic methods of PA determination feature a pre- or post-column derivatization step because many amines do not absorb in the UV region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple analytical methods have been developed to determine these compounds in various foods and beverages. Many review papers have been written in recent years [ 40 , 41 , 42 ]. Chromatographic methods of PA determination feature a pre- or post-column derivatization step because many amines do not absorb in the UV region.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, Nalazek-Rudnicka and Wasik [ 47 ] determined selected BAs in different fruit wines; however, they were not detected in chokeberry. Some authors [ 38 , 40 ] suggested that, in the case of wines, the toxic impact of BAs is not connected to their high concentration, but to the consumption of large quantities of wine in a very short time.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive amounts of biogenic amines can cause adverse effects in humans, such as headaches, blood pressure changes, breathing disturbances, heart palpitation, and vomiting [33,34]. If nitrites are present, biogenic amines could be converted to nitrosamines, which are suggested to cause cancer [35].…”
Section: Biogenic Amine Productionmentioning
confidence: 99%
“…Interestingly, several BAs have been detected also in alcohol-free, non-fermented beverages such as plant milks (e.g., soymilk and oat milk), fruit juices, tea, and coffee; the concentrations in most of these examples are typically below 10 mg/kg, most often even blow 1 mg/kg [ 32 ]. The topic of BA detection in dairy products, including the required sample-pretreatment methods, is covered in detail in a review of 2022 by Moniente and coworkers [ 33 ].…”
Section: Introductionmentioning
confidence: 99%